2018
DOI: 10.3389/fpsyg.2018.01819
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind Development in School-Aged Left-Behind Children in Rural China

Abstract: The current study aimed to investigate differences in theory of mind between left-behind children and non-left-behind children in rural China and to examine the potential protective role of general reasoning ability in left-behind children’s theory of mind. Participants included 213 children aged 7.10–13.67 years (111 boys and 102 girls, M = 10.51 years, SD = 1.33), 101 of whom were left behind in rural areas by one or both migrating parents for at least 6 months. The Strange Stories task, a second-order false… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
0
9
0
1
Order By: Relevance
“…Left-behind children refer to minors who are left in rural areas under the guardianship of grandparents, relatives, or neighbors because of the long-term migrant work of both parents or one party ( Liang et al, 2018 ; Liu et al, 2018 ; Gao et al, 2019 ). In addition, left-behind children are mainly the product of the urban–rural dual structure, extensively existing in various developing countries (e.g., China; Sun et al, 2015 ; Shao et al, 2018 ; Qin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Left-behind children refer to minors who are left in rural areas under the guardianship of grandparents, relatives, or neighbors because of the long-term migrant work of both parents or one party ( Liang et al, 2018 ; Liu et al, 2018 ; Gao et al, 2019 ). In addition, left-behind children are mainly the product of the urban–rural dual structure, extensively existing in various developing countries (e.g., China; Sun et al, 2015 ; Shao et al, 2018 ; Qin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, nearly half of our patients being left-behind children and their migrating parents have limited communication with their children, often discussing only their children’s learning situations rather than their emotional state or peer interaction. These disadvantages increase their children’s anxiety about learning and have a negative effect the left-behind child’s emotional development, self-awareness, mental health, and social behaviors [ 2 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nearly half of our patients being left-behind children and their migrating parents have limited communication with their children, often discussing only their children's learning situations rather than their emotional state or peer interaction. These [2,36]. Motor symptoms and non-epileptic seizures are the most common symptoms in children with dissociative disorders, and multiple conversion symptoms are the norm [4,14].…”
Section: Logistic Regression For Variables Predicting Prognosismentioning
confidence: 99%
“…Ding et al (2021) reported that left-behind children aged 4-6 staying with one parent scored higher in receptive vocabulary than their peers who stayed with grandparents. Similarly, Liu et al (2018) reported that the development of theory of mind in schoolaged left-behind children was slower than the non-left-behind children. Overall, left-behind children, especially whose parents were both absent, scored lower in these cognitive and language tasks.…”
Section: Factors Influencing Children's Narrative Macrostructure Prod...mentioning
confidence: 93%